Conjugation of a Toll‐Like Receptor Agonist to Glycans of an HIV Native‐Like Envelope Trimer Preserves Neutralization Epitopes. (20th June 2022) - Li, Zeshi; Derking, Ronald; Lee, Wen‐Hsin; Bosman, Gerlof P.; Ward, Andrew B.; Sanders, Rogier W.; Boons, Geert‐Jan
Abstract: Small molecule adjuvants are attractive for enhancing broad protection and durability of immune responses elicited by subunit vaccines. Covalent attachment of an adjuvant to an immunogen is particularly attractive because it simultaneously delivers both entities to antigen presenting cells resulting in more efficient immune activation. There is, however, a lack of methods to conjugate small molecule immune potentiators to viral glycoprotein immunogens without compromising epitope integrity. We describe herein a one‐step enzymatic conjugation approach for the covalent attachment of small molecule adjuvants to N ‐linked glycans of viral glycoproteins. It involves the attachment of an immune potentiator to CMP‐Neu5AcN3 by Cu(I)‐catalyzed azide‐alkyne 1, 3‐cycloaddition followed by sialyltransferase‐mediated transfer to N ‐glycans of a viral glycoprotein. The method was employed to modify a native‐like HIV envelope trimer with a Toll‐like receptor 7/8 agonist. The modification did not compromise Env‐trimer recognition by several broadly neutralization antibodies. Electron microscopy confirmed structural integrity of the modified immunogen. Abstract : Viral glycoprotein immunogens can be modified by a small molecule adjuvant by chemical attachment of an immune‐potentiator to CMP‐Neu5AcN3 followed by transfer to N ‐glycans of the glycoprotein. The method was employed to modify a native‐like HIV envelop trimer with an agonist of Toll‐like receptor 7/8. The modification did not compromise structural integrity and Env‐trimer recognition by several broadly neutralization antibodies.